Investigation Of Children Which Conflicting With Law In Narcotics Criminal Acts In Law Area Of The Semarang City Police Jurisdiction - Oscar Stefanus Setjo; Umar Ma'ruf (Jurnal Daulat Hukum, 2020)
The purpose of this study to know and analyze the mechanisms used in the investigation of children in conflict with the law against narcotic crime, the provision of diversion for children who are in conflict with the law in narcotic crime, obstacles and solutions in the process of diversion for children who are in conflict with the law in narcotics. This research uses the approach method of normative juridical and sociology juridical methods, the specifications in the study are analytical descriptive, population and sampling methods are all objects or all symptoms or all events or all units to be studied, data collection techniques using literature studies and interviews, analysis the data used are qualitative, using the theory of law enforcement, the theory of expediency and the theory of justice. Research result: Act No. 11 of 2012 on the Child Criminal Justice System. Giving diversion for criminal acts without victims also must be diversified. Crimes without victims such as narcotics abuse, children who become narcotics abusers are categorized as victims. Internal barriers, agreement between the victim and the child in conflict with the law; Human Resources (HR). External barriers, limited facilities and infrastructure; Different understandings; Lack of coordination; Community understanding of diversion; Regulation regarding supervision of the implementation of the agreed version of the agreement. Efforts to overcome internal barriers: Develop a work plan, include training investigators and educate. Efforts to overcome external barriers: Optimize facilities and infrastructure; Using social welfare personnel in the diversion process; Establish intensive communication with other law enforcement officers; Improve coordination with community mentors; Hold socialization.Keywords: Investigation; Children; Legal Conflict; Criminal Acts; Narcotics.